Effect of Hump Configurations of Porous Square Cavity on Free Convection Heat Transfer (Diyala Journal of Engineering Sciences, 2023)
Free convection is widely used in engineering applications, including solar energy, electronic devices, nuclear energy and heat exchangers. A computational simulation utilising Ansys Fluent-CFD was used to examine the natural convection heat transfer inside a square cavity filled with pure water and saturated metal foam as a porous medium (porosity ɛ=0.9). The enclosure’s lower wavy wall exhibits a high temperature (Th), whereas the side and upper walls display a low temperature (Tc). For different Rayleigh numbers, the study examines hump configuration and the bottom wall hump number (N). The predominant design of heat transmission was improved using the circular hump design parameters of ɛ=0.9, N=4 and Tc=25 °C for different Ra. The novelty of the research included determining the optimal design for the square enclosure. This approach involved estimating the effects of hump configuration and the number of humps for the bottom wall of the enclosure. These parameters have not been studied yet. The optimum case showed the highest heat transfer coefficient (h) at the circular hump, N=4 and Ra=30´103, whereas the standard case obtained N=0 and Ra=5´103. The CFD simulation results indicate that the primary objective of the study was achieved through the optimal design, resulting in a significant enhancement of hydrothermal performance for heat transfer enhancement and energy enhancement 1.13 times compared with the standard case.